Ethical Aspects of Patient’s Advanced Directives - Machinek, Marian Szczepan (Studia Warmińskie, 2019)
To many people, the perspective of being artificially kept alive while no longer capable of deciding their own fate is so disturbing, that they are extremely anxious to make provisions for such future situation in form of advanced directives. They are legal documents stating the author’s wishes concerning their health care in the event when they cannot make those wishes known. Closely linked to the entire issue of the relationship between patient and physician, modern concept of medical science and the place and role of ethics in it. The patient’s advance declaration may be critical in time of making medical decisions whether to apply or withhold extraordinary medical measures in his treatment. The patient himself gains a moral certitude that any medical intervention attempted during his mental and/or physical incapacity will be in concord with his specific wishes. It may establish and nurture mutual trust between patient and medical personnel. But they are also some ethical restriction concerning such documents. The future patients who are still healthy in moment of signing of the advanced directives can hardly make an accurate assessment of their hypothetical future situation. They may be influenced by many different factors first of all fear of prolonged suffering. Important is also the question whether advance directives concern terminal illness and end-of-life care only, or any prolonged state of unconsciousness of the patient? Some voices propose the institutions of the institution of Durable Power of Attorney as an alternative proposal to advanced directives.